Machine learning-based identification of SOX10 as an immune regulator of macrophage in gliomas - Xiao, Gelei; Wang, Kaiyue; Wang, Zeyu; Dai, Ziyu; Liang, Xisong; Ye, Weijie; Luo, Peng; Zhang, Jian; Liu, Zaoqu; Cheng, Quan; Peng, Renjun (Frontiers in Immunology, 2022)
Gliomas, originating from the glial cells, are the most lethal type of primary tumors in central nervous system. Standard treatments like surgery have not significantly improved the prognosis of GBM patients. Recently, immune therapy of glioma has provided us a novel and effective option. As a conserved group of transcriptional regulators, SOX family have been revealed to have the correlation with numerous diseases. Based on the large-scale machine learning, we found that SOX family can be divided into two distinct clusters in gliomas, with significant immune characteristics and genomic profiles. Among them, SOX10 was identified as an excellent immune regulator of macrophage in gliomas. High expression of SOX10 is related to shorter OS in LGG, HGG, and pan-cancer groups, but benefited from the immunotherapy. Single-cell sequencing proved SOX10 is high in neurons, M1 macrophages, and neural stem cells. Macrophages are found to be elevated in the SOX10 high expression group. SOX10 has a positive correlation with macrophage cytokine production and negative regulation of macrophages' chemotaxis and migration. In conclusion, our study demonstrates the outstanding cluster ability of the SOX family, and indicating that SOX10 is an immune regulator of macrophage in gliomas, which may be an effective target for glioma immunotherapy.